2007
DOI: 10.1177/10534512070420050101
|View full text |Cite
|
Sign up to set email alerts
|

Visual Supports for Students With Behavior and Cognitive Challenges

Abstract: In many schools, supports for children with a dual diagnosis of mental retardation and behavioral disorders are inadequate or nonexistent. Often these students are placed with teachers who, although appropriately trained and licensed, are not familiar with support strategies for meeting the behavioral and emotional needs of these students at an appropriate cognitive representational level. This article describes six evidence-based visual support strategies, their benefits, and simple methods for implementing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Each participant demonstrated an immediate level change for duration of problem behavior from baseline to intervention. Numerous studies have demonstrated the efficacy of visual supports, systematic instructional strategies, and positive reinforcement for individuals with severe disabilities (e.g., Banda, Grimmett, & Hart, 2009;Jaime & Knowlton, 2007;Odom, Collet-Klinenberg, Rogers, & Hatton, 2010). The results of this study support these previous findings but also provide preliminary evidence that suggests these same practices can be applied to teaching SWPBIS Tier 1 behavioral expectations in inclusive schoolwide settings.…”
Section: Discussionsupporting
confidence: 83%
“…Each participant demonstrated an immediate level change for duration of problem behavior from baseline to intervention. Numerous studies have demonstrated the efficacy of visual supports, systematic instructional strategies, and positive reinforcement for individuals with severe disabilities (e.g., Banda, Grimmett, & Hart, 2009;Jaime & Knowlton, 2007;Odom, Collet-Klinenberg, Rogers, & Hatton, 2010). The results of this study support these previous findings but also provide preliminary evidence that suggests these same practices can be applied to teaching SWPBIS Tier 1 behavioral expectations in inclusive schoolwide settings.…”
Section: Discussionsupporting
confidence: 83%
“…Teachers who use visual strategies increase learning structure and predictability and improve comprehension for students with and without disabilities when accessing the general curriculum, including students with ASD (Lequia et al, 2012), students with ADHD (Taylor & Villanueva, 2014), students with LD (Swanson, Lussier, & Orosco, 2015), students with emotional and behavioral disorders (EBD; Taylor & Villanueva, 2014), and students with ID (Jaime & Knowlton, 2007). Employing visual strategies during instruction can lead to positive student outcomes in the areas of social, communication, behavior, play, cognitive, school readiness, academic, motor, and adaptive skills (Wong et al, 2014).…”
Section: Research-based Strategiesmentioning
confidence: 99%
“…The illustrations and the story presented in a simple language in this comic book provide additional visual and textual supports that will benefit both students with and without disabilities, especially if they are struggling readers or readers with significant cognitive delays and challenging behaviors (Jaime & Knowlton, 2007). By increasing all students' comprehension and participation, teachers will also be able to nurture acceptance and inclusive behaviors in the classroom.…”
Section: Educating About Disabilitiesmentioning
confidence: 99%
“…For example, students with hearing impairments will benefit from hearing the information being presented through sign language or an interpreter. Students having learning disabilities will value the information presented in more than one modality, such as when a teacher uses visual strategies (e.g., handouts, diagrams, or graphic organizers) in addition to a more traditional discussion (Kluth, 2008;Jaime & Knowlton, 2007). Chandler-Olcott (2008) suggests using note-taking guides and direct teacher modeling to assist students in making visual inferences when reading comics.…”
Section: Educating About Disabilitiesmentioning
confidence: 99%